Navigating carbon neutrality pathway beyond energy and economic agents: the influence of media liberty across the OECD countries - Umut Uzar; Kemal Eyuboglu; Andrew Adewale Alola (Environmental Research Communications)
Press freedom is a fundamental aspect of democratic societies, playing a critical role in shaping public discourse, fostering transparency, and holding institutions accountable. Furthermore, its impact extends beyond political and social realms to encompass environmental sustainability, particularly in Organisation for Economic Co-operation and Development (OECD) countries. While extensive research has been conducted on the economic, social, and institutional factors that influence environmental outcomes, the role of press freedom in shaping ecological footprint remains underexplored. However, this study aims to address this gap by examining the relationship between press freedom and ecological footprint across 36 OECD countries from 2013 to 2022. Utilizing a system generalized method of moments (GMM) analysis and controlling for economic growth, trade openness, and energy consumption, this research reveals significant findings. Specifically, it demonstrates that press freedom serves as a catalyst for reducing ecological footprint, presenting OECD countries with a unique opportunity for environmental gains and potentially achieving carbon neutrality. In contrast, we find indicators such as economic growth, energy consumption, and trade openness have negative impact on environmental quality. Overall, this study underscores the importance of promoting press freedom as a key strategy for advancing environmental sustainability and calls for concerted efforts to harness its potential for mitigating ecological footprint in OECD countries and beyond.